The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1988
DOI: 10.1007/bf02388401
|View full text |Cite
|
Sign up to set email alerts
|

High resolution ultrasonography of the parotid gland in children. Part II

Abstract: The authors previously have reported a technique for visualizing the parotid gland with high resolution ultrasonography. The fine morphology of the parotid gland as well as normal anatomical landmarks were well visualized with ultrasonography. This study has continued for the past two years, and an additional twenty patients with suspected parotid pathology are presented. Ultrasound was helpful in (1) making a specific diagnosis in sialectasis, (2) determining whether parotid swelling was secondary to enlargem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Usually ultrasonography frequently demonstrates a marked increase in the size of the gland and usually shows hypoechoic areas consistent with parotitis. Ultrasonography is also helpful in determining whether a parotid swelling has arisen secondary to enlargement of adjacent tissue or to the presence of an intraglandular mass, including an abscess [20,21]. The differential diagnosis include facial cellulitis, cervical or preauricular lymphadenitis, osteomyelitis, subcutaneous fat necrosis and abscess formation, buccinators muscles infection, haemangioma, adenoma, lipoma [9,22].…”
Section: Discussionmentioning
confidence: 99%
“…Usually ultrasonography frequently demonstrates a marked increase in the size of the gland and usually shows hypoechoic areas consistent with parotitis. Ultrasonography is also helpful in determining whether a parotid swelling has arisen secondary to enlargement of adjacent tissue or to the presence of an intraglandular mass, including an abscess [20,21]. The differential diagnosis include facial cellulitis, cervical or preauricular lymphadenitis, osteomyelitis, subcutaneous fat necrosis and abscess formation, buccinators muscles infection, haemangioma, adenoma, lipoma [9,22].…”
Section: Discussionmentioning
confidence: 99%
“…The authors therefore recommended ultrasonography as the primary investigation for diagnosis, in addition to follow up. An earlier study had also found ultrasonography useful,35 though a direct comparison between conventional sialography, digital subtraction sialography, and ultrasonography had found ultrasonography less sensitive than the other two for inflammatory changes and sialolithiasis 34. It is possible that improvements in radiological skills and equipment may have now rendered ultrasonography as reliable as sialography.…”
Section: Investigationsmentioning
confidence: 98%
“…In acute bacterial sialadenitis, sonography reveals enlarged, hypoechoic glands with convex borders. [58][59][60][61] In acute inflammation of a salivary gland, the question sonography should answer is whether an abscess or obstructive sialadenitis is present. Abscesses are usually more or less hypoechoic lesions, with no perfusion in the fluid-filled center and a surrounding area of hyperperfusion on color Doppler imaging.…”
Section: Inflammatory Diseasesmentioning
confidence: 99%